(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Diabetes mellitus is the single most important metabolic disease which affects most of the organs in the body. It is the commonest endocrine disease found in general population. It is a syndrome (a collection of disorders in which hyperglycemia is the hall mark). Diabetes mellitus is characterized by hyperglycemia either due to a deficiency of insulin secretion or insulin resistance or a combination of both.